Advancing Aquaculture with Daphnia: Insights into Production, Nu-tritional Profile, and Benefits for Fish Larvae - Tohap Simangunsong; Hanisya Putri Kania Mardika; Rudy Wijaya (Journal of Aquaculture and Fish Health, 2026)
Daphnia, a genus of planktonic crustaceans, has gained significant attention in aquaculture due to its high nutritional value and suitability as live feed for fish larvae. This review synthesizes current research on Daphnia production, nutritional variability, and its role in enhancing fish larvae development. Numerous research findings indicate that the protein content of Daphnia provided to different fish larvae ranges from 40% to 60%. We explore the advancements in culture techniques, including the use of organic manures, microalgae, and probiotics, to optimize Daphnia yield and nutritional quality. The review highlights the benefits of Daphnia in improving fish larvae growth, survival rates, and immune response, while also addressing its role in nutrient recycling and water quality management. However, large-scale production faces challenges such as environmental sensitivity, limited shelf life, and competition with other live feeds. Sustainable practices, including the use of closed recirculating systems and bioencapsulation, are essential to mitigate ecological impacts and ensure long-term viability. By integrating current knowledge and identifying research gaps, this review underscores the potential of Daphnia as a sustainable and effective live feed in aquaculture, while calling for further innovation to overcome existing challenges.